2019
DOI: 10.3390/cancers11081103
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor Xa Promotes Solid Tumor Growth, Experimental Metastasis and Endothelial Cell Activation

Abstract: Hypercoagulable state is linked to cancer progression; however, the precise role of the coagulation cascade is poorly described. Herein, we examined the contribution of a hypercoagulative state through the administration of intravenous Coagulation Factor Xa (FXa), on the growth of solid human tumors and the experimental metastasis of the B16F10 melanoma in mouse models. FXa increased solid tumor volume and lung, liver, kidney and lymph node metastasis of tail-vein injected B16F10 cells. Concentrating on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In addition, restraining of its function retards cancer growth and metastasis [106]. Protease-activated receptors (PAR) and their downstream signaling factors, such as RhoA, are triggered by thrombin and FXa and responsible for the stimulation of endothelial hyperpermeability and metastasis [107,108]. The new findings suggested that TF in PCC-derived EVs activates ECs and converts them into inflammatory phenotypes via the FXa-PAR1 axis.…”
Section: Tissue Factormentioning
confidence: 99%
“…In addition, restraining of its function retards cancer growth and metastasis [106]. Protease-activated receptors (PAR) and their downstream signaling factors, such as RhoA, are triggered by thrombin and FXa and responsible for the stimulation of endothelial hyperpermeability and metastasis [107,108]. The new findings suggested that TF in PCC-derived EVs activates ECs and converts them into inflammatory phenotypes via the FXa-PAR1 axis.…”
Section: Tissue Factormentioning
confidence: 99%
“…Subsequently, cancer cells migrate out of the bloodstream by the process of extravasation and establish metastatic foci at distant organs (223). Fundamental to both these processes is endothelial permeability, which is promoted by the coagulation factors thrombin and FXa (15,224). Interestingly, recent studies have shown that autophagy is involved in thrombin-induced endothelial dysfunction.…”
Section: Coagulation Cascade and Autophagy In The Tumor Endotheliummentioning
confidence: 99%
“…Interleukin-8 (IL-8) and IL-6 (14), allowing the PARs to mediate several processes in the coagulation-inflammation interplay, including those implicated in cancer progression (15,16). Thus, PARs regulate platelet activation, assist in maintaining vascular barrier function through adhesion molecules (17,18), and are associated with immune cell activation and migration (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations